Children's Oncology Group's 2013 blueprint for research: Central nervous system tumors. Issue 6 (19th December 2012) - Gajjar, Amar; Packer, Roger J.; Foreman, N.K.; Cohen, Kenneth; Haas‐Kogan, Daphne; Merchant, Thomas E.
Abstract In the US, approximately 2, 500 children are diagnosed annually with brain tumors. Their survival ranges from >90% to <10%. For children with medulloblastoma, the most common malignant brain tumor, 5‐year survival ranges from >80% (standard‐risk) to 60% (high‐risk). For those with high‐grade gliomas (HGGs) including diffuse intrinsic pontine gliomas, 5‐year survival remains <10%. Sixty‐five percent patients with ependymoma are cured after surgery and radiation therapy depending on the degree of resection and histopathology of the tumor. Phase II trials for brain tumors will investigate agents that act on cMET, PDGFRA, or EZH2 in HGG, DIPG, or medulloblastoma, respectively. Phase III trials will explore risk‐based therapy stratification guided by molecular and clinical traits of children with medulloblastoma or ependymoma. Pediatr Blood Cancer 2013; 60: 1022–1026. © 2012 Wiley Periodicals, Inc.